On the influence of temperature on crystalline silicon solar cell characterisation parameters. (February 2015) - Ghani, F.; Rosengarten, G.; Duke, M.; Carson, J.K.
Highlights: The influence of temperature on the characterisation parameters of a silicon crystalline cell investigated. A numerical approach developed by the authors was applied to determine all five characterisation parameters. Current–voltage data experimentally acquired from a cell under different temperatures. Qualitative data presented showing the effect of temperature on each characterisation parameter. Abstract: The crystalline silicon type cell is at present the most commonly used photovoltaic device on the market. These solid state devices are only capable of converting a portion of the solar spectrum into electricity. Disregarding reflection losses, the remaining portion is absorbed by the cell thus elevating its operating temperature. It has been shown in a number of previous studies that the overall electrical performance of these cells will deteriorate with temperature, with power output dropping linearly with temperature. In this study, we examine this issue in closer detail by investigating how temperature affects each of the five characterisation parameters required to characterise their electrical behaviour using the single diode five parameter model. Collecting current–voltage data from a mono-crystalline silicon cell at constant irradiance but at temperatures varied within the range of 25 and 70 °C (the typical range experienced in the field), we calculated the five modelling parameters using a unique numerical approach which takes into consideration several points taken from the experimental current–voltage data. It was found that all five modelling parameters were influenced by temperature, with the reverse saturation current followed by the series and shunt resistances being affected most significantly, in that order. Photovoltaic device modelling will be enhanced by taking into account the influence of temperature on each of these characterisation parameters.